Modulation of IKKβ with AMPK Improves Insulin Sensitivity in Skeletal Muscle - Bikman, Benjamin Thomas (East Carolina University, 2008)
Activation of the insulin receptor substrate (IRS)-1 is necessary for proper transduction of the insulin signal. IRS-1 serine312(human)/307(rodent) phosphorylation, however, results in disruption of this signal and subsequent insulin resistance. Inflammatory mediators, such as the inhibitor of kappaB kinase beta; (IKK-beta), interrupt insulin signaling within insulin-sensitive tissues, such as skeletal muscle. In contrast, AMP-activated protein kinase (AMPK), a key metabolic enzyme, increases insulin sensitivity. To study the association of IKK-beta and AMPK, muscle biopsies were taken from post-bypass patients and control subjects. Post-bypass patients displayed similar levels of IKK-beta action and IRS1-pSer312 as the lean subjects and reduced levels compared with weight-matched control and morbidly obese subjects, which supports evidence that IKK-beta phosphorylates IRS-1 Ser312 and reduces the insulin signal, resulting in reduced whole-body insulin sensitivity. However, these findings did not correlate with baseline differences in AMPK phosphorylation. To explore the role of AMPK in attenuating IKK-beta activity and ameliorating insulin resistance, lean and obese Zucker rats were treated with metformin, an AMPK activator. Despite no differences at baseline, AMPK action was increased with metformin treatment in a fiber-type specific (white muscle) manner with a reduction in IKK-beta activity and IRS1-pSer307 in the muscle of obese rats only. To explore this relationship further, myotubes from lean and morbidly obese humans were exposed to the saturated fatty acid palmitate in the presence or absence of AICAR to activate AMPK. In contrast to the lean, obese myotubes demonstrated no depression in insulin signaling with lipid exposure. Co-incubation with AICAR prevented the lipid-induced decay of the insulin signal in the lean and improved the signal in the obese. AICAR-stimulated AMPK activation for the final 4 h of lipid exposure was not sufficient to restore phosphorylation of AS160. These data support the hypothesis that lipids induce insulin resistance via lipid-sensitive serine kinases that attenuate insulin signaling. Whereas AMPK activity does not appear to play a role in baseline differences of IKK-beta action and insulin signaling, we present findings that the lipid-induced decay in the insulin signal can be prevented by acute activation of AMPK. These results provide valuable information explaining differences in skeletal muscle function in the lean and obese, as well as elucidating a potential mechanism for insulin-sensitizing, AMPK-activating agents.
Keywords: Skeletal muscle; Insulin signaling; Insulin sensitivity; IKK-beta; AMPK; Biology; Physiology; Biology, Physiology; Insulin resistance; Insulin--Receptors